Climate adaptation in regional planning in Germany - Schmitt, Hanna Christine (AESOP, 2017)
The legal basis of the German spatial planning system is the Federal Planning Act (Raumordnungsgesetz des Bundes, ROG), which defines the core task of spatial planning to be the “anticipatory, comprehensive, supra-local and cross-sectoral organisation of the spatial and settlement structure for the medium and long term” (ARL, 2005, p. 965). Within the German planning system, regional planning is the intermediate level of comprehensive planning, bridging the (political) frameworks of the national level, sectoral planning and the (practical) implementation at the local level. It concretises the aims and guiding principles of comprehensive spatial planning of the national and federal-state level for all planning regions and prepares regional plans in accordance with § 8 (1) no. 2 ROG. Due to regional planning’s comprehensive, supra-local and yet spatially-specific character, it is qualified for addressing impacts of climate change. This becomes especially valuable in the light of absence of a separate sectoral planning division responsible for considering climatic changes (ARL, 2013; BMVBS, 2009; Federal Government, 2008).
Book of proceedings: Annual AESOP Congress, Spaces of Dialog for Places of Dignity, Lisbon, 11-14th July, 2017